Special types of graphic papers - Gregor Svetec, Diana; Szentgyörgyvölgyi, Rozália; Grilj, Silva; Debeljak, Mirica (Anali PAZU, 2022)
Presented research work is based on the determination of structure and properties of special printing papers, evaluation of their printability and suitability for digital printing. Synthetic papers, which are divided in the film synthetic papers and fiber synthetic papers belong to special printing papers, as well as papers made from 100% recycled fibers. In the article the printing properties of two types of synthetic papers and 100% recycled paper are presented.
Keywords: recycled paper; synthetic paper; printability